The effects of sprint training and the Nordic hamstring exercise on eccentric hamstring strength and sprint performance in adolescent athletes. - Freeman, Brock W; Young, Warren B; Talpey, Scott W; Smyth, Andrew M; Pane, Calvin L; Carlon, Todd A (Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Hamstring strain injuries (HSI) are among the most common injuries in field-based team sports with a high-speed running component. The implementation of the Nordic hamstring exercise (NHE) is a well-documented method of improving eccentric hamstring strength to mitigate the risk of HSI occurrence. Sprint training is specific to the injury mechanism and is thought to activate the hamstrings through maximal eccentric contractions. The purpose of this study was to compare the effects of sprint training and the NHE on eccentric hamstring strength and sprint performance., METHODS: Twenty-eight participants (mean+/-SD age=16.21+/-1.34 years; height=1.75m+/-0.10m; body mass=68.5kg+/-12.1kg) completed an eccentric hamstring strength assessment and 40m sprint to assess acceleration and maximum speed. Participants were randomly allocated to either a NHE training or sprint training group. Two sessions per week for four-weeks of training was performed with baseline testing procedures repeated in the week following the intervention. Perceptions of soreness were recorded following the warm-up in each training session., RESULTS: Both the NHE (effect size=0.39, P<0.05) and sprint training (effect size=0.29, P<0.05) groups displayed significant gains in eccentric hamstring strength. The NHE group reported trivial improvements in sprint performance, whilst the sprint training group experienced a moderate improvement, specifically in maximum speed (ES=0.83 Moderate). Sprint training also produced greater perceptions of soreness than the NHE following a four-week training intervention, specifically before the start of the last session (P<0.05)., CONCLUSIONS: These findings indicate that sprint training had a beneficial effect for both eccentric hamstring strength and sprint performance, whilst also producing greater soreness than the NHE following the final training session. It was concluded that a four-week block of maximum speed training may have both an injury prevention and performance enhancement benefit.
36 citations (Crossref) [2023-10-31] Place: Italy Freeman, Brock W. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia - brockw.freeman@gmail.com. Young, Warren B. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia. Talpey, Scott W. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia. Talpey, Scott W. School of Health and Human Services, Southern Connecticut State University, New Haven, CT, USA. Smyth, Andrew M. School of Health Sciences and Psychology, Faculty of Health, Federation University Australia, Ballarat, Australia. Pane, Calvin L. Maribyrnong Sports Academy, Melbourne, Australia. Carlon, Todd A. Maribyrnong Sports Academy, Melbourne, Australia.
Keywords: *Hamstring Muscles/ph [Physiology]; *Muscle Strength/ph [Physiology]; *Running/ph [Physiology]; Adolescent; Athletic performance; Exercise; Exercise Test; Exercise Test/mt [Methods]; Exercise/ph [Physiology]; Female; Hamstring Muscles; Hamstring muscles; Humans; Male; Muscle Strength; Resistance training; Risk Factors; Running; Soft Tissue Injuries; Soft Tissue Injuries/et [Etiology]; Soft Tissue Injuries/pc [Prevention & Control]; Sports medicine; acceleration; accident prevention; adolescent; article; athlete; athletic performance; clinical article; controlled study; dept.hhs; eccentric muscle contraction; effect size; exercise; exercise test; female; hamstring muscle; human; male; muscle strength; peer-reviewed; perception; physiology; procedures; randomized controlled trial; resistance training; risk factor; running; soft tissue injury; sports medicine; warm up

Ten-year trends and differences in alcohol consumption among black and white female undergraduates - Barton, Barbara A; Bulmer, Sandra Minor; Mugno, Raymond; Misencik, Leann (Journal of Substance Use, 2019)
Background: Few studies have explored changing patterns of alcohol consumption among young females and differences based on race/ethnicity. Objective: This study examined differences in alcohol consumption between black and white undergraduate females and compared trends in three different measures of alcohol consumption over a 10-year period from 2004 to 2014. Methods: The CORE Alcohol and Drug Survey was used to collect data from female undergraduates attending a public university in the northeastern USA. Classes were randomly selected into the sample; class acceptance was 68% and student participation was 96%. The chi-square test examined differences between groups and the Cochrane Armitage Test for Trend assessed changes over time. Results: In 2014, for every measure of alcohol consumption examined, a significantly larger percentage of white females engaged in the behavior compared to black females. Trend analysis from 2004 to 2014 demonstrated a narrowing of this gap. Controlling for age, any alcohol use in past 30 days and binge drinking in the past 2 weeks increased significantly for black females 21 years or older. Any alcohol use in the past 30 days decreased significantly for white females under 21 years. Conclusion: These findings introduce many questions which should be explored through additional research.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-626-859-619-803 tex.type: [object Object]
Keywords: Alcohol; Article; Black person; Caucasian; United States; adult; alcohol; alcohol consumption; binge drinking; college females; dept.hhs; dept.mat; dept.pch; drinking trends; female; human; major clinical study; peer-reviewed; priority journal; race difference; undergraduate student